The Linking of Emotional Intelligence and Team Performance: The Mediating Role of Knowledge Sharing - Nguyen, Thi-Trang-Nhung (Current Topics on Business, Economics and Finance Vol. 6, 2023)
The research that examined the connections between emotional intelligence, knowledge sharing, and team effectiveness is outlined in this article. The study also investigated the impact of emotional intelligence and knowledge sharing on team performance. Although these interactions are crucial for improving team performance, there aren't many empirical research that look at these interactions together. This study used data from 357 employees of SMEs in Vietnam to analyze those associations using SEM. The obtained data were analyzed using SPSS and AMOS Version 22. Results from a test of these relationships largely support our hypothesized model. The findings showed that through encouraging knowledge sharing, emotional intelligence indirectly improves team performance. Furthermore, knowledge sharing has a direct impact on how well a team performs. On the other side, there is a strong correlation between sharing knowledge and emotional intelligence. The study's findings, implications, and suggestions for further study are explored.